The Construction of Interpersonal Meaning Realized in a Conversation between EFL Students - Bagus Dwi Pambudi; Djoko Sutopo; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2022)
Interpersonal meaning enables speakers to create a conversation by taking roles and establishing relationships. This study attempts to explain how interpersonal meaning is constructed in a conversation between EFL students by focusing on (1) how they take up roles, (2) how they establish relationships, and (3) how the roles and relationships are negotiated. This qualitative study involved a small group of three university students taking part in a conversation within an informal setting. This study drew on analyses on moods, speech functions, and conversational exchanges based on the theory suggested by Eggins and Slade (2004). The results indicate that mood choices allowed the students to take two main roles: initiator and supporter. The initiating role was realized in full declaratives and full interrogatives. The supporting role was achieved through minor clauses, elliptical clauses, and giving opportunities and assistance to the others to deal with incomplete clauses. The speech function choices show that the students established harmonious relationships because they frequently sustained their talks and provided support instead of confrontation. However, this does not seem to represent a good-quality conversation as they tended to avoid different ideas to explore relationships. The way the students in turn showed dominance indicates that they negotiated roles and relationships dynamically. This study can provide a new insight to improve EFL students’ ability to participate in a conversation.